Leadership Preparation Programs: Preparing Culturally Competent Educational Leaders. (September 2019) - Barakat, Maysaa; Reames, Ellen; Kensler, Lisa A. W.
The demographic profile of the United States has been rapidly changing; by 2020, minority students will constitute the majority of the public school student population nationwide. This makes cultural competence a necessity for today's school leaders. Educational leadership preparation programs are responsible for preparing culturally competent leaders; however, few programs assess their students' cultural competence. The purpose of this quantitative, cross-sectional, causal-comparative study was to examine whether graduates of educational leadership preparation programs had significantly different cultural competence than those beginning their respective program. The findings of this study suggest that matriculating through a principal preparation program positively correlates with educational leadership students' overall cultural competence, cultural beliefs and motivation, and cultural knowledge. However, there appears to be no significant relationship between completing the program and students' cultural skills.